(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the epidemiological and cytopathological profile of cervical cancer diagnosed in the period from 2016 to 2019, in Teresina, Piauí. Methodology: For the production of this study, an epidemiological study of a descriptive nature was carried out, with a quantitative and retrospective approach. The collected data were related to the city of Teresina, Piauí, Brazil. These data were collected through secondary data, extracted from SISCAN, from the Department of Informatics of the Unified Health System (DATASUS). To identify the scientific evidence about women’s knowledge about the preventive exam, a search for articles published in scientific journals available online at Scielo and Lilacs was carried out. Results and Discussion: After collecting and analyzing the data, it was possible to identify that the city of Teresina presented, between the period from 2016 to 2019 and in the age group 15 to 65 years, a total of 104,966 cytopathological exams, with a significant increase each year. The predominant age group where there was a greater number of exams performed was 35 to 39 years old with about 14,761 (14%) exams. Among the benign cellular alterations (reactive or repair), inflammation was the most frequent finding, about 67,949 (64.7%) exams. Conclusion: The present study showed that the frequency of exams showed a significant increase, with great age variation, with a decline in the incidence of cervical cancer. It was also noted that the lack of information on the part of many women is a factor that hinders the frequency of exams.